“If Necessary for Years, If Necessary Alone”: History, Memory, and Fiction in Contemporary Representations of Dunkirk - Malvestio, Marco (Status Quaestionis, 2020)
A seemingly impossible task, the evacuation of the majority of the British Expeditionary Force (more than 300,000 men) from the shores of Dunkirk, besieged by the German forces, represented a symbol of hope in a moment in which the British Empire was suffering crushing defeats in Europe as well as in Asia. The myth of the ‘finest hour’ of the British people, both spontaneously generated from below and directed from above by the government, has been a central topic of the British propaganda during and after the war, and it still possesses a strongly evocative power over new generations of artists. In recent years, several movies (Atonement, 2007, Dunkirk, 2017, Darkest Hour, 2017) have represented the evacuation of Dunkirk, oscillating between propagandistic rhetoric and a problematization of the memory of the war. By analyzing these films, this article shows how post-war generations have appropriated the cultural memory of Dunkirk as a way of restaging an ideal of Britishness and at the same time as a controversial attempt to update it by highlighting the divisions of class and ideology among British society and the army.